Methadone maintenance treatment program in prisons from the perspective of medical and non-medical prison staff: a qualitative study in Iran - Moradi, Ghobad (Int J Health Policy Manag, 2015)
Background: As one of the most important components of harm reduction strategy for high-risk groups, following the HIV epidemics, Methadone Maintenance Treatment (MMT) has been initiated in prisoners since 2003. In this paper, we aimed to assess the advantages and shortcomings of the MMT program from the perspective of people who were involved with the delivery of prison healthcare in Iran. Methods: On the basis of grounded theory and through conducting 14 Focus Group Discussions (FGDs), 7 FGDs among physicians, consultants, experts, and 7 FGDs among directors and managers of prisons (n= 140) have been performed. The respondents were asked about positive and negative elements of the MMT program in Iranian prisons. Results: This study included a total of 48 themes, of which 22 themes were related to advantages and the other 26 were about shortcomings of MMT programs in the prisons. According to participants’ views "reduction of illegal drug use and high-risk injection", "reduction of potentially high-risk behaviors" and "making positive attitudes" were the main advantages of MMT in prisons, while issues such as "inaccurate implementation", "lack of skilled manpower" and "poor care after release from prison" were among the main shortcomings of MMT program. Conclusions: MMT program in Iran’s prisons has achieved remarkable success in the field of harm reduction, but to obtain much more significant results, its shortcomings and weaknesses must be also taken into account by policy-makers.